2016
DOI: 10.1021/acs.chemrev.6b00204
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Transition Metal Hydrides

Abstract: Photochemical reactivity associated with metal-hydrogen bonds is widespread among metal hydride complexes and has played a critical part in opening up C-H bond activation. It has been exploited to design different types of photocatalytic reactions and to obtain NMR spectra of dilute solutions with a single pulse of an NMR spectrometer. Because photolysis can be performed on fast time scales and at low temperature, metal-hydride photochemistry has enabled determination of the molecular structure and rates of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
115
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 317 publications
5
115
0
Order By: Relevance
“…Our earlier conclusion that 1b is the E 2 (2H) state with its reducing equivalents stored as a bound hydride 4,6,9 is corroborated by the observation that the E 2 /1b state is photoactive, like inorganic hydride complexes, 17,18 the [Fe–H–Fe] bridging hydrides of the E 4 (4H) state of nitrogenase, 19,20 and the [Ni–H–Fe] bridging hydrides of the Ni–C state of NiFe hydrogenase. 21 As noted above, the earlier cryoannealing study of E 4 (4H) implied that the hydride of E 2 /1b adopts a [Fe–H–Fe] bridging structure, and it will be thus described in this report.…”
Section: Resultsmentioning
confidence: 71%
“…Our earlier conclusion that 1b is the E 2 (2H) state with its reducing equivalents stored as a bound hydride 4,6,9 is corroborated by the observation that the E 2 /1b state is photoactive, like inorganic hydride complexes, 17,18 the [Fe–H–Fe] bridging hydrides of the E 4 (4H) state of nitrogenase, 19,20 and the [Ni–H–Fe] bridging hydrides of the Ni–C state of NiFe hydrogenase. 21 As noted above, the earlier cryoannealing study of E 4 (4H) implied that the hydride of E 2 /1b adopts a [Fe–H–Fe] bridging structure, and it will be thus described in this report.…”
Section: Resultsmentioning
confidence: 71%
“…This effect could be understood by photoinduced reductive elimination of H 2 followed by oxidative addition of p-H 2 . Photochemical loss of phosphine competing with loss of H 2 was also observed for Ru(H) 2 (PMe 3 ) 4 . 27 The time scales available and the sensitivity of TRIR spectroscopy have improved greatly since our 1997 study, and there are no longer any gaps in the nanosecond time domain.…”
Section: ■ Introductionmentioning
confidence: 65%
“…4 One of the earliest metal hydrides to be studied photochemically was Ru(H) 2 (CO)(PPh 3 ) 3 (1) (Scheme 1), a compound of great interest for its catalytic properties both under illumination and by thermal means. 5−13 The original studies of its photochemistry demonstrated loss of H 2 , but not CO, on irradiation in benzene.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The redox‐active photosensitizers available include organic dyes,3 inorganic clusters,4 and transition‐metal complexes, such as [Ru(bpy) 3 ] 2+ and its derivatives,5, 6 whose redox potentials can be fine‐tuned by ligand modification 7, 8, 9. Photoredox catalysis can bypass reactive stoichiometric oxidants, such as H 2 O 2 and ClO − , to generate high‐valent transition‐metal oxido species by electron‐transfer oxidation.…”
mentioning
confidence: 99%
“…Photoredox catalysis can bypass reactive stoichiometric oxidants, such as H 2 O 2 and ClO − , to generate high‐valent transition‐metal oxido species by electron‐transfer oxidation. Non‐heme iron complexes that are well‐known catalysts for a wide range of oxidation reactions have been combined with photoredox catalysts, such as [Ru(bpy) 3 ] 2+ , for light‐driven oxidation reactions 9, 10, 11. In this multicatalyst strategy (Scheme 1 a), excitation of the photoredox sensitizer is followed by electron‐transfer oxidation of the catalyst to raise it to a higher oxidation state so that it can subsequently oxidize substrates.…”
mentioning
confidence: 99%